Knowledge Sharing Behavior and Job Satisfaction: Exploring the Psychological Function of Employee Counseling in Indonesian Bureaucracy - Vizra Hukama; Arum Etikariena; Alya Aqilah Madhani; Nor Shafrin Ahmad (Universitas PGRI Yogyakarta, 2026)
This study investigates the relationship between knowledge-sharing behavior and job satisfaction among Indonesian civil servants, with hierarchical organizational culture as a moderator. Set within Indonesia’s context of bureaucratic reform, this research highlights how structural and cultural changes shape public sector performance. While knowledge sharing is linked to innovation and well-being, inconsistent findings suggest that contextual factors, especially hierarchy, influence its effect on satisfaction. Using a quantitative cross-sectional design, 203 civil servants from various institutions with at least two years of experience participated. Data from an online survey were analyzed using Pearson correlation and moderated regression (Hayes PROCESS Model 1). Results show that knowledge sharing positively predicts job satisfaction (b = .1691, p < .01), meaning exchanging knowledge enhances psychological fulfillment. However, hierarchical culture significantly and negatively moderates this relationship (b = –0.1161, p < .05), indicating that rigid, authority-driven environments reduce the benefits of knowledge exchange. Additionally, older and longer-tenured employees report higher satisfaction and alignment with hierarchical norms, while better-educated individuals show lower satisfaction and weaker cultural alignment. These findings emphasize the psychological role of knowledge sharing in public institutions and highlight the need for reforms promoting autonomy, open communication, and counseling-based support to improve employee well-being and performance within Indonesia’s bureaucracy. Keywords: bureaucratic reform, civil servants, hierarchical culture, Indonesia, job satisfaction, knowledge sharing, organizational psychology